2017
DOI: 10.5455/njppp.2017.7.0414006052017
|View full text |Cite
|
Sign up to set email alerts
|

Liver enzymes in obstructive sleep apnoea syndrome

Abstract: Background: Obstructive sleep apnea syndrome (OSAS) is a common form of sleep disordered breathing. OSAS is associated with the cluster of metabolic abbreations that comprise the metabolic syndrome, including nonalcoholic fatty liver disease. Aims and Objectives: We investigated the effects of OSAS and its treatment with short term nasal continuous positive airway pressure (CPAP) therapy on serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels. Materials and Methods: We studied 20 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For instance, in animal models mimicking OSA treated with NAC, oxidative stress and liver inflammation were attenuated [ 50 ], pancreatic β cells were protected from apoptosis [ 51 ], pharyngeal muscle dilator performance was also improved [ 52 ], and diaphragm muscle dysfunction was prevented [ 53 ]. In addition, oral administration of NAC to patients with OSA improved sleep efficiency, shortened the duration of apneas, decreased lipid peroxidation, and increased total reduced glutathione [ 54 ]. Taken together, these findings demonstrate the protective effects exerted by the antioxidant NAC against IH-induced oxidative stress, inflammation, and overall improving OSA associated consequences.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in animal models mimicking OSA treated with NAC, oxidative stress and liver inflammation were attenuated [ 50 ], pancreatic β cells were protected from apoptosis [ 51 ], pharyngeal muscle dilator performance was also improved [ 52 ], and diaphragm muscle dysfunction was prevented [ 53 ]. In addition, oral administration of NAC to patients with OSA improved sleep efficiency, shortened the duration of apneas, decreased lipid peroxidation, and increased total reduced glutathione [ 54 ]. Taken together, these findings demonstrate the protective effects exerted by the antioxidant NAC against IH-induced oxidative stress, inflammation, and overall improving OSA associated consequences.…”
Section: Resultsmentioning
confidence: 99%
“…This condition is considered a proinflammatory vascular risk factor and NAC has been thought to improve this [ 93 ]. There are small clinical RCT trials that have shown benefit [ 94 , 95 ].…”
Section: Metabolic Syndrome Including Nonalcoholic Fatty Liver Disease Diabetes and Polycystic Ovarymentioning
confidence: 99%
“…Of note, contractile and endurance properties are equivalent in male and female sternohyoid muscle under control conditions. Given the association of hypoxia with oxidative/nitrosative stress and muscle functional adaptation in patients and animal models (Lavie 2003, Zhu et al 2003, Koechlin et al 2005, Ottenheijm et al 2006, Marin-Corral et al 2009, Sadasivam et al 2011, Skelly et al 2012a, Shortt et al 2014, the sex differences reported herein may relate to differences in the cellular response to redox stress. One study highlights stronger defenses against oxidative stress in female rat liver, heart, brain, and kidney tissues compared with males (Katalinic et al 2005).…”
Section: Molecular Mechanisms That Drive Contractile Differencesmentioning
confidence: 83%